Institutional capacity for EU Cohesion Policy: Concept, evidence and tools that matter. - Busetti, Simone; Pacchi, Carolina (Routledge, 2014)
The article provides a thorough investigation of the concept of institutional capacity applied to the case of EU Cohesion Policy. It presents part of the results of the SMART-IST project, funded under the ESPON Program, which comprised nine case studies across eight European regions. The article proposes and discusses three possible notions of institutional capacity: 1.) the ability to come to terms with EU rules and procedures, 2.) the capacity to use EU funds and procedures to bring forth local projects and strategies, 3.) the capacity to use the competences built through managing EU policies in order to improve the overall quality of public administrations. Capacity building tools supporting such three types of capacity are presented and their effectiveness in improving capacity is discussed with respect to the evidence collected across the case studies.
Keywords: Raumplanung; Region; Regionalpolitik; Kohäsion; Planungsziel; Planungsinstrument; Personalplanung; Kohäsionspolitik; EU-Projekt; Projektbericht; Europäisierung; Organisationsentwicklung; Institutionalisierung; Regional Governance